Benefiting from Asia’s Technology Revolution [Invited Paper] - Lord, John (Journal of Telecommunications and the Digital Economy, 2019)
An invited paper, the Charles Todd Oration 2019, delivered by Mr John Lord AM that covers how Australia might benefit from Asia’s technology revolution.